Empirical correlation of PGA, spectral accelerations and spectrum intensities from active shallow crustal earthquakes. - Bradley, Brendon A. (Earthquake engineering & structural dynamics.)
Empirical correlation equations between peak ground acceleration, spectral acceleration, spectrum intensity, and acceleration spectrum intensity are developed. The correlation equations are developed for shallow crustal earthquakes using the Next Generatin Attenuation (NGA) ground motion database, and four of the NGA ground motion prediction equations (GMPEs). And particularly novel aspect of the present study is the explicit consideration of epistemic uncertainty in the correlation equations due to both the adopted ground motion database and GMPEs. The resulting correlation equations enable the joint consideration of these four ground motion intensity measures in ground motion selection using framework such as the generalized conditional intensity measure approach.